PENGARUH BERMAIN SOLITARY PLAY TERHADAP PROSES PENYEMBUHAN ANAK USIA 2-3 TAHUN DENGAN FEBRIS DHF DI BANGSAL TERATAI RUMAH SAKIT DR. OEN SURAKARTA - Setyaningsih, Rahayu; Ningsih, Endang Dwi (KOSALA : Jurnal Ilmu Kesehatan, 2013)
Background Playing is an activity that can be done as an effort to stimulate thechild's growth and development. Playing for the children at hospital can be amedium to express feelings of relaxation and distract of discomfort due toillness.The purpose of this study was determine the effect of playing therapy withsolitary paly on healing process of children aged 2-3 years with DengueHemorragic Fever who hospitalized at Teratai ward of Dr.Oen Surakarta.Methods This study used a pre-experiment design with one shot case studyapproach. The playing therapy was done in 8 patients consisted 3 boys and 5girls. Data were collected using an observation sheet. Data processing used tteststatistical test with significance level Î± : 0.05.The conclusion The result showed t count > t table (2.379 > 2.365). It can beconcluded that solitary play therapy gave significant effect fever at Teratai ofDr.Oen Surakarta hospital.Keywords : Play Therapy, Healing Process